Effectiveness assessment of sulfur-containing amino acids in rats with experimental "alcohol withdrawal syndrome" with modified zoosocial interaction methods - V. I. Petrov; N. A. Osadchenko; A. S. Tarasov; A. M. Dotsenko; E. I. Morkovin (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2024)
The aim of the work was to compare the effects of ademethionine, acetylcysteine and taurine on the zoosocial behavior of rats in a post-intoxicated state after an acute ethanol poisoning.Materials and methods. The study was conducted on male rats of the Wistar line. The post-intoxication state was modeled by a single injection of ethanol (3 g/kg, intraperitoneally). 30 min after awakening, the animals were injected with a physiological solution, acetylcysteine (1 g/kg), ademetionine (100 mg/kg) or taurine (40 mg/kg). A zoosocial interaction test was performed 30 min after the administration.Results. Among the behavioral indicators investigated, the following were validated: the number of acts of freezing, their duration, the number of acts of sniffing in front, the number of acts of avoidance and the number of vertical stances without support (p <0.05 between the values of the negative and positive control groups in all cases). The administration of acetylcysteine, ademetionine and taurine reduced the number of freezing acts by 53.64, 7.27 and 24.51%, respectively (p <0.05 when compared with the indicator index in the animals from the positive control group in all cases). The administration of acetylcysteine and taurine reduced the number of avoidance acts by 50 and 10%, respectively (p <0.05 when compared to that of the animals from the positive control group in both cases). All amino acids normalized the communicative performance, although it did not differ from that of the animals from the positive control group (p >0.05). Alcoholization reduced the number of vertical stances by 65% (p <0.001 when compared with that in the animals from the negative control group), and when followed by the administration of ademetionine and taurine, the reduction was 38 and 36%, respectively (p <0.05 when compared to that in the animals from the negative control group).Conclusion. According to the data obtained, sulfur-containing amino acids, primarily those that had central effects, normalized neuronal functions, positively influencing a complex behavior of rats. Taking into account the results of the previous studies, it was possible to conclude that the therapeutic effect of ademetionine and taurine in the context of a post-intoxication state is mediated by their central effects, which are not so pronounced in comparison with acetylcysteine.